1951
DOI: 10.1007/bf02589702
|View full text |Cite
|
Sign up to set email alerts
|

Surface tension determinations of some saturated fat acid methyl esters

Abstract: Summary Methyl esters of saturated naturally occurring fat acids from C6 through C18 were prepared and purified by fractional distillation. Refractive indices were used as a measure of their purity. A micro surface tension apparatus was constructed to comply with a modified capillary rise method devised by Ferguson. The surface tensions of water and of benzene were determined at several temperatures. The results obtained compared quite favorably with the values listed in the International Critical Tables. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Length of Headgroup. Changes in either the size or the configuration of the alkyl headgroup in alkyl methyl esters has been shown to dramatically effect properties such as cloud point, pour point, , and lubricity. , The surface tensions of the methyl ester, ethyl ester, and fatty acids of many oleochemicals have been reported, but not much has been done with larger headgroups. The difference between methyl and ethyl esters is quite small, always within 0.5 mN m -1 at 75 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Length of Headgroup. Changes in either the size or the configuration of the alkyl headgroup in alkyl methyl esters has been shown to dramatically effect properties such as cloud point, pour point, , and lubricity. , The surface tensions of the methyl ester, ethyl ester, and fatty acids of many oleochemicals have been reported, but not much has been done with larger headgroups. The difference between methyl and ethyl esters is quite small, always within 0.5 mN m -1 at 75 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Many valuable surface studies have been done on saturated fatty acids or esters, while much less has been reported on their unsaturated , counterparts and none is available for epoxidized fatty ester materials. Herein, we report the surface tensions of various epoxidized oleochemicals (Figure ), including epoxidized methyl oleate (EMO; methyl 9,10-epoxy stearate), epoxidized methyl linoleate (EMLO; methyl 9,10,12,13-diepoxy stearate), and epoxidized soybean oil methyl esters (ESME), as well as similar results for a comparable set of the parent olefins.…”
Section: Introductionmentioning
confidence: 99%
“…Probably, the large discrepancy (0.45%) of the data reported by Nevin et al 28 is due to the effect of impurities on the measured properties or incorrect calibration of the instrument. These data 28 are systematically higher than the present, and all other reported data by 0.28%. All reported speed of sound data points (32 data points) [24][25][26]32 for methyl laurate (see Table 1), except for the data reported by Tat and van Gerpen, 1 were included in the primary set.…”
Section: Speed Of Soundmentioning
confidence: 86%
“…Due to their inconsistency, some data sources were excluded from the primary set. For example, Nevin et al 28 (3 data points) was excluded from the primary data due to a large discrepancy (within 0.2−0.3%) with other reported data. The purity of the studied samples has not been provided by the authors.…”
Section: Speed Of Soundmentioning
confidence: 99%
See 1 more Smart Citation